2009
DOI: 10.1021/la9017689
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Dendrimer Sensors: Probing the Diffusion of an Explosive Analogue Using Neutron Reflectometry

Abstract: Determining how analytes are sequestered into thin films is important for solid-state sensors that detect the presence of the analyte by oxidative luminescence quenching. We show that thin (230 +/- 30 A) and thick (750 +/- 50 A) films of a first-generation dendrimer comprised of 2-ethylhexyloxy surface groups, biphenyl-based dendrons, and a 9,9,9',9'-tetra-n-propyl-2,2'-bifluorene core, can rapidly and reversibly detect p-nitrotoluene by oxidative luminescence quenching. For both the thin and thick films the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 27 publications
3
58
0
Order By: Relevance
“…More recently, fluorescent dendrimers have shown substantial potential as explosive sensing materials [12][13][14][15][16][17][18] owing to their high photoluminescence quantum yields, monodispersity and the ability to control and tailor the physical properties through tuning of the chemical structure. For the photoluminescence (PL) to be quenched, the fluorophore and the quencher have to be close enough to allow electron transfer to occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, fluorescent dendrimers have shown substantial potential as explosive sensing materials [12][13][14][15][16][17][18] owing to their high photoluminescence quantum yields, monodispersity and the ability to control and tailor the physical properties through tuning of the chemical structure. For the photoluminescence (PL) to be quenched, the fluorophore and the quencher have to be close enough to allow electron transfer to occur.…”
Section: Introductionmentioning
confidence: 99%
“…However, while neutron reflectometry can be used to follow the analyte desorption for a thermally activated process it does not have the sensitivity or time resolution to measure the A c c e p t e d M a n u s c r i p t 3 sorption of the analyte, which is when the initial response of the sensor is triggered [14,18,19]. In this study, we have utilized a custom-built experimental setup enabling time-resolved quartz crystal microbalance (QCM) measurements to monitor the analyte uptake in dendrimer sensing films, thus providing important information about the diffusion behaviour for such materials.…”
Section: Introductionmentioning
confidence: 99%
“…2,24 On the flipside, fluorescent probe based method harnessed from photoluminescence (PL)-based chemosensors possess unparalleled sensitivity, selectivity, low instrumentation cost, portability, short response time, and dual compatibility in solid and solution media. 5,[30][31][32] Several luminescent probes have been explored as fluorescence based explosive-sensors till date, 12,22,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] but their multi-step processing, toxicity and lack of control over molecular organization limits their wide use. 8,51 In fact, literature reports on fluorophore probe-based explosive sensing in water have been indeed scarce.…”
mentioning
confidence: 99%
“…The diffusion of the pNT into a sensing film has recently been studied by neutron reflectivity. 22 The neutron reflectivity data showed that the pNT caused the sensing film to swell and that diffused essentially through the whole film. It may be that lower vapor pressure DNT and DNB effectively 'precipitate' in the film and are not as good plasticizers as the high vapor pressure pNT.…”
Section: Solid State Quenchingmentioning
confidence: 99%